Meta-Analysis: Effectiveness of Dental and Oral Health Education using Combination Method on Knowledge and Plaque Scores in Visually Impaired Childrenveness of Dental and Oral Health Education using Combination Method on Knowledge and Plaque Scores in Visually Impaired Children - Anis Nur Widayati; Didik Gunawan Tamtomo; Burhannudin Ichsan (Journal of Health Promotion and Behavior, 2024)
Background: Dental health education is important to improve people's dental and oral health. Visually impaired children have limited vision, so they need appropriate and appropriate methods for accepting visually impaired children by maximizing the provision of education through senses other than sight in carrying out treatment and prevention efforts. This study aimed to analyze the effectiveness of combination oral health education on the oral health knowledge and plaque scores in visually impaired children. Subjects and Method: This was a meta-analysis with PICO model. Population: Visually impaired children. Intervention: dental health education ≥3 methods. Comparison: without education or <3 education methods. Outcome: oral hygiene knowledge and plaque scores. Article search was carried out using the keywords: ("dental health education" OR "oral hygiene" OR "oral health education") AND ("visually impaired children" OR "blind children") AND “randomized control trial”. Studies published between 2013-2023 from the PubMed, Elsevier, Google Scholar, and Science Direct databases were included. Standarized mean difference (SMD) from selected articles were were analyzed using the Review Manager 5.4 tool. Results: 10 RCTs from India and Indonesia were included in the meta-analysis. The use of combined education methods increased knowledge of oral hygiene compared to single education (SMD= 2.67; 95% CI= 1.05 to 4.30; p<0.001). Combined education method reduced plaque scores compared to single education (SMD= -0.82; 95% CI= -1.29 to -0.35; p<0.001). Conclusion: Combination education methods increase oral hygiene knowledge and reduce plaque scores in visually impaired children.